2016
DOI: 10.1017/s1049023x16000091
|View full text |Cite
|
Sign up to set email alerts
|

First Responder Accuracy Using SALT during Mass-casualty Incident Simulation

Abstract: Primary care paramedics performed MCI triage more accurately than FS students after brief SALT training, but no difference was found regarding types of error or time to triage completion. The clinical importance of this difference in triage accuracy likely is minimal, suggesting that fire services personnel could be considered for MCI triage depending on the availability of prehospital medical resources and appropriate training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The best outcomes would be achieved with early triage that is efficient and precise. 4 The present results revealed that the START group of nonmedical personnel who were provided even a very brief training on the START triage protocol immediately before the exercise more accurately placed their patients into the correct triage color codes, whereas the non-START group exhibited a much higher deviation from the baseline representing an accuracy level of 100% exact triage of all "patients" (Figure 1).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The best outcomes would be achieved with early triage that is efficient and precise. 4 The present results revealed that the START group of nonmedical personnel who were provided even a very brief training on the START triage protocol immediately before the exercise more accurately placed their patients into the correct triage color codes, whereas the non-START group exhibited a much higher deviation from the baseline representing an accuracy level of 100% exact triage of all "patients" (Figure 1).…”
Section: Discussionmentioning
confidence: 61%
“…Over-triaging patients by assigning those who are not in critical condition as in need of immediate medical attention can overwhelm hospital facilities and medical professionals. 4,8 In this way, scarce resources are not effectively used to benefit patients truly in need of life-saving medical attention. Under-triage jeopardizes the single patient outcome, whereas over-triage risks incapacitating the whole emergency medical system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of effort has gone into creating effective triage teaching and training methods [65,72,148,149]. Courses such as ATLS and PHTLS have had an impact on trauma care education, and take place worldwide.…”
Section: Discussionmentioning
confidence: 99%